PERKULIAHAN AKUNTANSI BERBASIS DARING: DAMPAK SERVANT LEADHERSHIP DOSEN TERHADAP KEPUASAN MAHASISWA - Ririh Dian Pratiwi; Ngurah Pandji MAD (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
This study aims to determine the impact of the servant leadership of lecturers on student satisfaction in accounting lectures online. The servant leadership style has five dimensions including altruistic calling, emotional healing, wisdom, persuasive mapping, and organizational stewardship. This study uses a population of all Accounting students from one of the tertiary institutions in Semarang. Samples were obtained by random means with a sample size of 100 respondents obtained from calculations using the Slovin formula. Data were analyzed using Multiple Linear Regression analysis. This research obtained the result that the research model was stated well. Partially, only the wisdom and persuasive mapping variables that influence student satisfaction in accounting online-based lectures. While the other three independent variables, namely altruistic calling, emotional healing, and organizational stewardship, were not proven to affect student satisfaction. The limitation of this research is that the scope of the object used is limited, so it is expected that further research can expand the object, namely various universities in Semarang to be examined. Keywords: Servant leadership, satisfaction, accounting lectures